2015
DOI: 10.1002/ange.201506959
|View full text |Cite|
|
Sign up to set email alerts
|

An Experimentally Established Key Intermediate in Benzene Nitration with Mixed Acid

Abstract: Experimental evidence is reported for the first intermediate in the classic S E Ar reaction of benzene nitration with mixed acid. The UV/Vis spectroscopic investigation of the reaction showed an intense absorption at 320 nm (appearing as ab and shoulder) arising from ar eaction intermediate.O ur theoretical modeling shows that the interaction between the two principal reactants with solvent (H 2 SO 4 )m olecules significantly affects the structure of the initial complex. In this complex, al arger distance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the final step, we assumed the deprotonation of the scomplex by H 2 SO 4 molecules, which are the most abundant species in the solution system (s-complex + H 2 SO 4nitrobenzene + H 3 SO 4 + ). 16 Although the free energy change by deprotonation in the H 2 SO 4 solution was calculated as À23.8 kcal mol À1 as shown in the figure, deprotonation by other solvent molecules will be possible under the real experimental conditions. As an example, stabilisation due to the abstraction by HSO 4 À anions was À60.5 kcal mol À1 .…”
Section: Free Energy Surfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the final step, we assumed the deprotonation of the scomplex by H 2 SO 4 molecules, which are the most abundant species in the solution system (s-complex + H 2 SO 4nitrobenzene + H 3 SO 4 + ). 16 Although the free energy change by deprotonation in the H 2 SO 4 solution was calculated as À23.8 kcal mol À1 as shown in the figure, deprotonation by other solvent molecules will be possible under the real experimental conditions. As an example, stabilisation due to the abstraction by HSO 4 À anions was À60.5 kcal mol À1 .…”
Section: Free Energy Surfacesmentioning
confidence: 99%
“…Following previous considerations on basis sets and functionals, 5,14,16,17 free energy surfaces for nitration of benzene were evaluated using the density functional method with the M06-2X 36 functional and 6-311G(d,p) basis set. At first, geometry optimisations in solution were performed with the conductor-like polarisable continuum model (CPCM) 37,38 of the H 2 O solution.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…5g This result indicates that none of the other polar solvents could stabilize the π-complexes, which previously had only been observed in a nitric and sulfuric acid mixture. 18 In 2020, our group found that in PFTB, intramolecular epoxide-opening cyclization of an epoxy alcohol proceeds with endo selectivity and that the selectivity can be increased by adding 1 equiv of [EMIM]BF 4 (Scheme 2e). Using the [EMIM]BF 4 /PFTB combination, we were able to construct the skeleton of marine ladder polyethers in one step by means of endo-selective intramolecular cascading epoxide-opening cyclizations of polyepoxy alcohols.…”
Section: ■ Introductionmentioning
confidence: 99%